2013
DOI: 10.1111/hepr.12237
|View full text |Cite
|
Sign up to set email alerts
|

Sequential occurrence of acute hepatitis B among members of a high school Sumo wrestling club

Abstract: A 17-year-old male was admitted to our hospital and diagnosed with acute hepatitis B. Six weeks later, a 15-year-old male was admitted with acute hepatitis B as well. They were Sumo wrestling players in the same club. A detailed survey in the club revealed that a 28-year-old male coach was a hepatitis B surface antigen carrier with high-level viremia. The consistency of hepatitis B virus (HBV) DNA in the infected players was revealed by analyzing the complete HBV genome sequences. Sumo players are more likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although no epidemiological reports have indicated that athletes who take part in contact sports have a significantly higher prevalence of HBV infection [ 3 , 4 ], 3 previous case reports have shown HBV outbreaks among athletes who engage in contact sports, such as sumo wrestling and American football [ 5 7 ]. In all studies, the infections were presumed to have been transmitted horizontally from an index case to contacts via skin abrasions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no epidemiological reports have indicated that athletes who take part in contact sports have a significantly higher prevalence of HBV infection [ 3 , 4 ], 3 previous case reports have shown HBV outbreaks among athletes who engage in contact sports, such as sumo wrestling and American football [ 5 7 ]. In all studies, the infections were presumed to have been transmitted horizontally from an index case to contacts via skin abrasions.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of hepatitis B vaccination has been slower in Japan than in other countries. Three cases of horizontal transmission of HBV in contact sports have been previously reported in Japan [ 5 7 ]. The American Medical Society for Sports Medicine (AMSSM) has issued an advisory to alert clinicians regarding the risk of transmission of blood-borne pathogens such as HBV by contact sports [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although post-transplant HBV vaccination is an alternative that may provide a chance to discontinue prophylaxis by producing anti-HBs, close monitoring of serum HBV markers is needed. Furthermore, based on the fact that Japanese adults are not obligated to undergo HBV vaccination (22), pre-transplant HBV vaccination is crucial for potential recipients of LT in Japan (19).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1.34 million people died from viral hepatitisrelated chronic liver disease or hepatocellular carcinoma (HCC) in 2015, which was comparable to deaths caused by tuberculosis and higher than those caused by human immunodeficiency virus (HIV) [2]. Transmission of hepatitis viruses, such as HBV, has been documented by non-conventional routes among athletes participating in contact sports like wrestling [3][4][5] and football [6] due to close contact of the subjects and bleeding from combat activities and collisions occurring in any contact sport [7,8]. The risks of transmission of hepatitis viruses among elite athletes are hard to quantify owing to the scarcity of data in the literature.…”
Section: Introductionmentioning
confidence: 99%